A Validation Study for Services Provided by Aanganwadi Centers in Raipur City - Sharma, Mini; Soni, G P; Sharma, Nitin (National Journal of Community Medicine, 2013)
Introduction: It has been a focus of interest to expand ICDS scheme and provide adequate quality of services to the beneficiaries. Current study is an attempt to find out the coverage deficit in services provided by Aanganwadi centers to its eligible beneficiaries residing under urban project of Raipur district (I & II). Objective: The study was conducted to validate the service provided to the eligible beneficiaries by the concerned Aanganwadi centre. Materials and methods: Cross sectional observational study conducted at Raipur district in selected 30 Aanganwadi centers [by Systemic random sampling]. Selected centers were visited & their infrastructure, facility, beneficiaries registers were checked.10% of beneficiaries identified and interviewed to check adequacy of services. Observations: 172/342(50 %) of the beneficiaries were not weighted when asked. 27/342(8 %) didn’t know that what the frequency of growth monitoring at their centre was? Only 54/86(63%) received preschool education when interviewed. There was a deficit in record keeping in 15/30(50%) of Aanganwadi centre. Cause of partial immunization was the uncooperative nature of their AWW. Conclusions: There was a gross deficit in the services provided by the Aanganwadi centers under ICDS scheme especially in record keeping when cross checked. This scheme is a social welfare scheme and a deficit like this is unacceptable.